2020
DOI: 10.1152/japplphysiol.00320.2020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elevated positive end-expiratory pressure on diaphragmatic blood flow and vascular resistance during mechanical ventilation

Abstract: This is the first study, to our knowledge, demonstrating that mechanical ventilation, with low and high positive end-expiratory pressure (PEEP), increases vascular resistance and reduces total and regional diaphragm perfusion. The rapid reduction in diaphragm perfusion and increased vascular resistance may initiate a cascade of events that predispose the diaphragm to vascular and thus contractile dysfunction with prolonged mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
0
12
0
1
Order By: Relevance
“…Greenough [19] believed that neonates should be subjected to simultaneous mechanical ventilation at a lower PIP to reduce lung trauma, air leakage, bronchopulmonary dysplasia and other problems. Horn [20] found that high PEEP would lead to reduced blood perfusion in the diaphragmatic muscle, thus affecting respiration in animal experiments. In summary, the relationship between mechanical ventilation and pneumothorax still needs further studies to explore.…”
Section: Discussionmentioning
confidence: 99%
“…Greenough [19] believed that neonates should be subjected to simultaneous mechanical ventilation at a lower PIP to reduce lung trauma, air leakage, bronchopulmonary dysplasia and other problems. Horn [20] found that high PEEP would lead to reduced blood perfusion in the diaphragmatic muscle, thus affecting respiration in animal experiments. In summary, the relationship between mechanical ventilation and pneumothorax still needs further studies to explore.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate shear stress, we used previously established in vivo medial costal diaphragm blood flow data from several studies 2,12,14 (Table 1) combined with in vitro vasomotor studies on isolated medial costal diaphragm blood vessels. We chose this approach due to the inability to perform both blood flow and isolated vessel experiments in the same tissue of the same animal (see Appendix for detailed methods).…”
Section: Methodsmentioning
confidence: 99%
“…In each animal, 1As arterioles from the medial costal diaphragm were used for the isolated vessel experiments and underwent passive‐pressure response experiments (described below). We chose to study medial costal diaphragm 1As, as the medial costal diaphragm receives the highest mass‐specific blood flow within the costal diaphragm 2,12,14,22 and previous research demonstrates MV‐induced vascular dysfunction in medial costal diaphragm 1As 4 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations